STATISTICAL EXAMINATION OF THE QUALITY OF GROUNDWATER IN A FEW VILLAGES IN COASTAL REGION OF SANTHABOMMALI (International Journal of Food and Nutritional Sciences, 2022)
After air, water is arguably the most valuable asset to humanity. Even while water covers up the majority of the earth's surface, relatively little of it is really exploitable, making it a very scarce resource. Thus, caution needs to be exercised in the usage of this valuable and finite resource. Water must be suitable preceding usage because it is used for a variety of uses. In order to assess whether water sources are healthy or not, regular monitoring is also necessary. In addition to being a sign of deteriorating environmental conditions, unhealthy water bodies pose harm to the ecology. Poor water quality in industries can lead to risks and significant financial loss. As a result, the condition of water has a significant impact on the environment and the economy. Analysing the quality of the water is therefore necessary before using it for any purpose. Evaluation of water quality today uses a few established techniques despite years of investigation. Sample collection, maintenance, and inspection are governed by certain rules. For the benefit of analysts and investigators, the normative sequence of operations is briefly outlined below. This study was conducted in five distinct villages in the santhabommali mandal of Srikakulam: Jagnnadhapuram, Mulapeta, Bavanapaadu, Kothalingudu, and Lakkivalasa Twenty groundwater samples that were collected during the pre-monsoon period were used in the study. Samples were collected from several bore wells and wells utilising an erratic testing procedure in an attempt to evaluate the chemical characteristics of the water quality parameters.